2010
DOI: 10.1007/s12011-010-8822-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Copper, Iron, Zinc and Fe 3 + Haemoglobin Levels on the Etiopathogenesis of Chronic Calcific Pancreatitis—A Study in Patients with Pancreatitis

Abstract: Chronic pancreatitis is a serious condition associated with severe abdominal pain, and a significant percentage of patients progresses to irreversible calcification in pancreas. The present study evaluates the degree to which the levels of trace elements, copper, iron, selenium, zinc and haemoglobin-Fe(3+), in blood, serum and pancreas have any role to play in the calcification process associated with fibrosis in pancreas. Twenty-seven calcific (CCP) and 23 non-calcific chronic pancreatitis (CP) patients and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Navarro et al showed that zinc deficiency is associated with collagen deposition and pancreatic fibrosis 16 . Supporting these findings, Geetha Armugam et al showed that reduced zinc levels and increased levels of copper and iron in the pancreatic tissue resected from CP patients may contribute to collagen deposition during the process of calcification 17 . Recently, ZnT2 (SLC30A2) has been implicated in Zn transport into zymogen granules of the pancreas which is required for the functioning of various proenzymes.…”
Section: Discussionmentioning
confidence: 86%
“…Navarro et al showed that zinc deficiency is associated with collagen deposition and pancreatic fibrosis 16 . Supporting these findings, Geetha Armugam et al showed that reduced zinc levels and increased levels of copper and iron in the pancreatic tissue resected from CP patients may contribute to collagen deposition during the process of calcification 17 . Recently, ZnT2 (SLC30A2) has been implicated in Zn transport into zymogen granules of the pancreas which is required for the functioning of various proenzymes.…”
Section: Discussionmentioning
confidence: 86%
“…Table 1 is a distillate of many studies in patients with chronic pancreatitis, itemised in earlier reviews (16,18,23,34), now incorporating more recent observations in patients with mainly alcoholic disease (138,5). The findings are readily rationalized by the electrophilic stress concept (Figure 1), but not by any other theory on pathogenesis (34).…”
Section: Cyp Induction / Concurrent Toxicantsmentioning
confidence: 99%
“…The information reveals that induction of the xenobiotic-processing machinery in liver and pancreas is not innocuous, despite mobilization of several natural antioxants (67,111). Studies on surgically resected specimens afford direct evidence of CYP induction (55,147,168), and also on-going oxidative stress : structural aberrations by microscopy ( Table 1) (24), FRA signals (155), increased FROP with decreased GSH (5,133), increased concentrations of prooxidant metals (copper, iron) but decreased levels of antioxidant metals (zinc, selenium) (5); and markers of the ER stress-UPR (123). The last finding might be expected to involve disrupted calcium homeostasis (177), but studies in isolated rat acini indicate that this is not a factor in toxicity from induced CYP (37).…”
Section: Cyp Induction / Concurrent Toxicantsmentioning
confidence: 99%
See 2 more Smart Citations